COMPARATIVE ANALYSIS OF UKRAINIAN AND GERMAN HIGHER EDUCATION SYSTEMS: EXPLORING CONTRASTS AND POTENTIAL COLLABORATIVE ENDEAVORS IN PROFESSIONAL PEDAGOGY (Comparative Professional Pedagogy, 2023)
This research article presents a comprehensive comparative analysis of the Ukrainian and German higher education systems, examining their distinctive characteristics and potential for collaboration in the field of professional pedagogy. The study delves into the structural variances, global rankings, admission requirements, tuition fees, research and innovation landscapes, internationalization efforts, and partnership prospects. By critically examining these aspects, this research contributes to the scholarly discourse on comparative education and professional pedagogy, shedding light on the significance of cross-national collaboration in shaping the future of higher education.In this article, we conducted a comprehensive review of academic literature, reports, studies, and relevant documents on the Ukrainian and German higher education systems, examined official documents, policies, and regulations from relevant governmental and educational bodies in both countries, utilized statistical data available from official sources, educational institutions, and international organizations to quantify and compare various aspects of the education systems, such as enrolment numbers, program offerings, research output, and internationalization efforts. In a larger scholarly context, this research makes a significant contribution to the discourse on comparative education and professional pedagogy. By adroitly navigating and dissecting the multifaceted domains of both systems, the research lays bare the underlying dynamics that shape their educational paradigms. The illumination of cross-national collaboration as an instrumental force in shaping the trajectory of higher education underscores the article's scholarly import. To sum up, this research advances the understanding of both systems, envisages novel collaborative trajectories, and underscores the scholarly imperative of cross-nation cooperation in shaping the future contours of higher education.
Keywords: comparative analysis; Ukrainian higher education system; German higher education system; collaboration; internationalization; research; professional pedagogy